Internalization of Moderation Values in Islamic Religious Education Subjects in SMP Negeri 22 Padang - Alfurqan Alfurqan; Ajat Hidayat (MANAZHIM, 2023)
This research aims to identify the values of moderation in the subject of Islamic Religious Education at SMP Negeri 22 Padang. This study uses a qualitative method with a qualitative descriptive approach. As a data source, the researchers selected 14 informants using a purposive sampling technique. The informants included one school principal, one curriculum representative, two Islamic religious education teachers, and ten students. Collecting data using observation, interviews, and documentation. Data were analyzed by reduction, presentation, and conclusion. This study found four values of moderation namely i`tidal by being assertive through the regulations and the evaluation stage, tasamuh by advising about tolerance, shura by familiarizing students with discussions and deliberations, and qudwah by making the teacher a good person to emulate. These four values are internalized using four methods namely being an example for students, doing habituation, giving advice, and telling stories.